Hubungan Tingkat Stres dengan Kualitas Tidur pada Mahasiswa Tingkat Akhir Dimasa Pandemi Penyakit COVID-19 di Universitas Harapan Bangsa, Purwokerto - Oktaviani, Fani Try; Apriliyani, Ita; Yudono, Danang Tri; Dewi, Feti Kumala (Health Information : Jurnal Penelitian, 2021)
Final semester students who are working on thesis often experience stressful events, especially during the COVID-19 disease, the learning system is carried out online, and experience sleep disturbances. The purpose of this study was to determine the relationship between stress levels and sleep quality in final semester students. The research design used quantitative methods, cross-sectional data collection, with a population of 66 students in the final semester of the nursing study program at Harapan Bangsa University. Data was collected using a Depression, Anxiety and Stress Scale (DASS-42) and Pittsburgh Sleep Quality Index (PSQI) questionnaire which were distributed online using a google form. The majority of respondents experienced mild stress (48.5%), and moderate sleep disturbances (71.2%). Data analysis used Spearman's-rank statistical test method, p value 0.001, and r 0.445. There is a relationship between stress levels and sleep quality for final year students at Harapan Bangsa University.